2008
DOI: 10.1007/s12029-008-9041-z
|View full text |Cite
|
Sign up to set email alerts
|

An Update on Advance Directives in the Medical Record: Findings from 1186 Consecutive Patients with Unresectable Exocrine Pancreas Cancer

Abstract: These findings underscore the ongoing need to discuss advance directives with patients with incurable malignancies and to clarify patients' wishes when seemingly contradictory information appears in other parts of the medical record.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
20
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(24 citation statements)
references
References 13 publications
3
20
0
1
Order By: Relevance
“…This was consistent with previous studies [11, 21, 33, 35]. Usually, the older cancer patients talk about the death much more than the younger patients, and most of them desire for death with dignity, but they are not sure how to die, therefore, they willing to use ADs to put their wishes on paper.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…This was consistent with previous studies [11, 21, 33, 35]. Usually, the older cancer patients talk about the death much more than the younger patients, and most of them desire for death with dignity, but they are not sure how to die, therefore, they willing to use ADs to put their wishes on paper.…”
Section: Discussionsupporting
confidence: 91%
“…Previous studies indicate that completion of ADs was 15 to 41 % among the cancer patients [11, 20, 21]; 9 to 70 % among older adults [2, 5, 16, 22]; 15 to 30 % among general population [23]; 7 % among hemodialysis patients [24]; 6 % among hematological malignancy patients [25]. Dow reported that 63 % of oncology patients did not know what an AD was [11], and Ewer doubted about the purpose and role of ADs [26].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…31 This is also consistent with a cohort of 1186 consecutive advanced pancreas cancer patients at the Mayo Clinic, wherein only 15% had an AD as part of the medical record. 32 One additional indication of patient wishes in the video arm (or one fewer in the narrative arm) would have made for statistical significance in our study.…”
Section: Epstein Et Almentioning
confidence: 94%